Caractérisation Des Paramètres Agroclimatiques Clés De La Saison Culturale En Zone De Contact ForêtSavane De Côte-d’Ivoire - Kouamé, Brou; Ehounou, Jean-Noël; Kassin, Koffi Emmanuel; Dekoula, Charles Sépka; Yao, Guy Fernand; N’goran, Emmanuel Kouadio; Kouakou, Brou Julien; Koné, Boaké; Soro, Nagnin (European Scientific Journal, ESJ, 2018)
In the Central region of Côte d’Ivoire, contact area between the South forest estate and savanna’s area in the North, the climate is a major concern for people. Since the late 1960s, the constant changes in rainfall amounts make it difficult for the various agricultural operations in the area. Before the natural instability of the rainfall regime and the extreme variability of agro-climatic parameters, farmers are no longer able to detect the probable dates of start and end of the rainy seasons that are essential to optimize agricultural production. From the descriptive statistical analysis of rainfall data from the stations of Bouaké, Béoumi, Katiola and Dabakala over the period 1961-2000, this study focuses on assessing the dynamics of agro-climatic key factors of the growing season in this transition zone. The results show an earlier start and a later end of the rainy season in Bouaké and Béoumi. On the contrary, the seasons started later and ended earlier in the localities of Katiola and Dabakala, and the dry sequences, during the rainy seasons, are longer in these localities.